The Tingkeban Tradition and Islam-Jawa Acculturation Among the Javanese Community in North Sumatra - Heny Fadillah; Hasnah Nasution (INTEGRASI : Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study aims to explore the Tingkeban tradition, which has undergone acculturation with religious values as a form of cultural adaptation among the Javanese community in North Sumatra. Its primary focus is on how the symbolic meanings of this tradition are perceived by Javanese people within the social environment in which they live. This research employs a qualitative method with a phenomenological approach to investigate in depth the practice of Tingkeban in Pangkalan Lunang Village, North Labuhanbatu. Primary data were obtained through observation, interviews, and documentation involving Javanese community members, religious leaders, and pinisepuh (customary elders). The findings show that Javanese migrants continue to preserve the Tingkeban tradition as an inherited cultural legacy, although its practice and meaning have shifted from those in the place of origin, even while its physical ritual elements still resemble the original form. Tingkeban is intended as a supplication for the safety of women who are seven months pregnant so that both mother and child may be granted health and protection. Each stage of the ritual is accompanied by prayers, shalawat, and dhikr, thereby integrating customary rites with Islamic principles.